1997
DOI: 10.1524/strm.1997.15.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Bayes Estimation of a Location Parameter

Abstract: Assume that in independent two-dimensional random vectors (Λι, θ\) ,..., (ΧΝ,ΘΝ), each Θϊ is distributed according to some unknown prior distribution density g, and that , given θ,, Xi has the conditional density function q(x -Θ,), i = 1,..., TV. In each pair the first component is observable, but the second is not. After the (JV+l)-th pair (X^r+i, is obtained, the objective is to construct the empirical Bayes estimator of a polynomial f(0w + 1) = with given coefficients bj. In the paper we derive the empir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
(27 reference statements)
0
9
0
Order By: Relevance
“…In the present problem, the regret of φ is equal to R n (y) f (y)dy with R n (y) given by (4.7). However, Pensky [11] pointed out at least two advantages of using (4.7) compared to the regret. First, R n (y) enables one to calculate the mean squared error for the given observation Y n+1 = y which is the interesting quantity.…”
Section: Empirical Bayes Estimator and Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present problem, the regret of φ is equal to R n (y) f (y)dy with R n (y) given by (4.7). However, Pensky [11] pointed out at least two advantages of using (4.7) compared to the regret. First, R n (y) enables one to calculate the mean squared error for the given observation Y n+1 = y which is the interesting quantity.…”
Section: Empirical Bayes Estimator and Main Resultsmentioning
confidence: 99%
“…In this paper, we study the performance of our EB estimator using the "mean squared error" (MSE) criterion. Our rationale to study the MSE of our EB estimator is motivated by the work of Pensky [11], where she has argued that MSE is a more appropriate criterion as far as applications are concerned. We will construct an EB estimator of β (for the unknown σ 2 case) based on some improved estimators of multivariate normal mixture density and its first partial derivatives.…”
Section: Introductionmentioning
confidence: 99%
“…Pensky (1997) studied empirical Bayes estimation of the location-parameter in a location-parameter family distribution. Li and Gupta (2001) studied an empirical Bayes test in a truncation parameter family distribution and showed that the proposed empirical Bayes test achieves the optimal rate of convergence.…”
Section: Introductionmentioning
confidence: 99%
“…Various methods of empirical Bayes estimation have been considered and estimates with different convergence rates have been obtained (see, for instance, [4,6,7,13,[15][16][17][18]). In this connection the question becomes significant: what is the best convergence rate that can be obtained for a [12]) and develop the ideas of her papers [9][10][11]. In this connection the question becomes significant: what is the best convergence rate that can be obtained for a [12]) and develop the ideas of her papers [9][10][11].…”
Section: Introductionmentioning
confidence: 99%